bk-5214S2L, an allelic variant of bk-5, as high-quality silage maize genetic resource - Li, Gang; Du, Jiyuan; Li, Xiaohu; Zhuge, Shilin; Ren, Shuolin; Wu, Min; Ma, Haoran; Guo, Xinrui; Chen, Ziqiang; Ding, Haiping (Frontiers in Genetics, 2025)
IntroductionStem brittleness significantly affects both yield and quality of maize.MethodsUsing phenotypic identification and sequence analysis, we identified a new brittle stalk maize mutant. Furthermore, we assessed its feeding value by content determination of cellulose, hemicellulose, lignin crude fiber, starch, and protein contents.ResultsHere, we identified a brittle stalk maize mutant, bk-5214S2L, an allelic variant of bk-5. The stem brittleness of bk-5214S2L was similar to that of bk-5, but not identical. Unlike bk-5, bk-5214S2L leaves did not fall off completely and its stems did not break in windy conditions. We identified a missense mutation (C>T) in the fifth exon of the candidate gene Zm00001d043477, resulting in an amino acid change from serine to leucine at position 214. A significant reduction in cell wall thickness in the leaf veins and stems of bk-5214S2L compared with the inbred line RP125. Among the major cell wall components in stems and leaves, total cellulose, hemicellulose, and lignin were lower in bk-5214S2L than in RP125. We also evaluated the application value of bk-5214S2L silage and found that the detergent fiber contents of bk-5214S2L stems were significantly reduced compared with RP125, while the crude fiber, starch, and protein contents remained unchanged. The reduced tannin content improved the palatability of the silage for livestock.ConclusionOverall, bk-5214S2L, an allelic variant of bk-5, is a high-quality genetic resource for breeding forage and grain-feed maize.